Arthur B. Davies, Sacramental Trees - Gephart, Emily (Conversations, 2014)
Two maidens, one bright and one shadowy, lead an ox through a curiously dense, shallow, and cubistically-fragmented woodland, heading (one presumes) through the titular sacramental trees and towards an uncertain destination.